2016
DOI: 10.1597/14-062
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors at Age 10: Psychological Adjustment in Children with a Cleft Lip and/or Palate

Abstract: Objective To explore psychological functioning in children with a cleft at age 10 from a broad perspective, including cognitive, emotional, behavioral, appearance-related, and social adjustment. High-risk groups were identified within each area of adjustment to investigate whether vulnerable children were found across domains or whether risk was limited to specific areas of adjustment. Methods Retrospective chart review from psychological assessments at age 10 (N = 845). The effects of gender, cleft visibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 66 publications
(117 reference statements)
7
55
1
Order By: Relevance
“…Therefore, it is essential for a cleft team to include assessments of PRO and psychosocial outcome into standard practice of care [32]. To enable cleft teams to learn as much as possible from a wide variety of experience, it is desirable for cleft teams to use an internationally accepted outcome measure [1,7,17,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is essential for a cleft team to include assessments of PRO and psychosocial outcome into standard practice of care [32]. To enable cleft teams to learn as much as possible from a wide variety of experience, it is desirable for cleft teams to use an internationally accepted outcome measure [1,7,17,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The same author, however, in a further study highlighted that self-reported psychosocial functioning in patients with CL/ P was worse than in non-cleft controls, when analysed in separate domains of depressive symptoms, behavioural problems and satisfaction with appearance and speech [11]. Further studies have suggested that self-reported psychosocial function significantly correlates with satisfaction with appearance [7,[12][13][14] and speech [4,[15][16][17]. Hearing difficulties have also been associated with social impairment [17].…”
Section: Patient Satisfaction With Hearing Appearance and Speech Andmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, body image has received increasingly more attention in medical populations, particularly those which impact physical appearance (Fauerbach et al, 2000; Bowe et al, 2011; Clarke et al, 2014; Auerbach et al, 2014; Sarwer, et al 2006). While condition-specific measures have been developed (e.g., Satisfaction with Appearance Scale; Emerson, et al, 2004), there is little consensus about which measures to use when assessing body image and psychosocial functioning among youth with visible differences (Feragen & Stock, in press; Roberts & Shute, 2011). Instruments developed for the general population may not be sensitive enough to identify specific concerns (e.g., concerns about facial features).…”
Section: Introductionmentioning
confidence: 99%